Substance Addiction in Urban Adolescents of District Ghaziabad - Agrawal, Deepika; Jetli, Neha; Gupta, Gajendra K; Singh, Anupama; Zaidi, Syed Nawaz (Indian Journal of Community Health, 2024)
Background: Substance abuse is an important problem in today’s world as it causes considerable physical and mental suffering. In India, adolescents are considered as a pillar of the nation as they are responsible for its future progress. Therefore, substance abuse control among this age group becomes even more important. Objectives: To find the prevalence, patterns and gender association of substance abuse among adolescents in urban areas of district Ghaziabad. Methods: A cross-sectional study was conducted in the schools of urban areas of district Ghaziabad. 750 adolescents including equal number of boys and girls were selected randomly from the co-education schools. A questionnaire was administered to assess the baseline information. MS Excel 2020 and SPSS were used to arrive at statistical conclusions. Results: Addicting substance was abused by 64.8% males and 33.9% females and this difference in proportions was statistically significant (p-value =0.001). The maximum number of study participants got encouragement to start the usage of addictive substances from their peers (33.0%). Four-fifths (80.3%), of the substance abusers had the desire to quit. Conclusion: In the present study, 33% of the participants started abusing addictive substances under peer pressure. School-based awareness, health education and motivation among the adolescents is the need of the hour. Role of student counsellors may prove fruitful and bring about the desired behavioural change.